(untitled) (R&E-SOURCE, 2014)
Mathematics teaching and learning process expectedly should portray an interactive and dynamic classroom experience capable of promoting mathematical understanding and sustaining learners’ interest in anticipation of applying what they have learnt. This study, being quasi-experimental, therefore expands the empirical base for understanding learners’ cognitive load memory capacity in relation to use of graphical materials on students’ mastery of mathematics concept of Set Theory. The sample consisted of seventy-five (75) students from the selected schools in Egbeda, Oyo State. Three research hypotheses were tested using t-Test statistics. Evidence from field survey indicates that students were more enthusiastic in classroom because of the interactive nature portrayed by the graphical materials. Results also indicated that students taught with the aid of graphical materials, that is, the experimental group, had significantly higher mean gain score and it was recommended that, teachers should begin the use of graphical materials as opportunity to make the learning of mathematics easier and that, if properly harnessed, this aspect of instruction may serve as simulator helping learners construct meanings and develop their own understanding, ready to take on more complicated structures as they moves towards complex concepts in mathematics.